PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN PARTISIPASI SHOLAT ZUHUR BERJAMAAH KELAS 7 SMPN 3 KERTEK - Angger Arya Maulana; Asep Sunarko; Nasokah Nasokah (JURNAL ILMIAH NUSANTARA, 2026)
Islamic Religious Education teachers play a strategic role in encouraging students' active participation in congregational prayer activities at school. This study aims to describe the role of Islamic Religious Education (PAI) teachers in motivating 7th-grade students at SMPN 3 Kertek to perform Zuhr prayer in congregation, analyze the implementation of participation enhancement programs, and identify supporting and inhibiting factors in the process. This research used a qualitative descriptive method with observations, interviews, and documentation as data collection techniques. The data analysis followed Miles and Huberman’s interactive model including data reduction, data display, and conclusion drawing. The results show that PAI teachers carry out integrated roles as educators, motivators, role models, and guides, resulting in a 90% student participation rate, with half of them proactively going to the mosque without being instructed. The program is implemented through a shift-based rotation system, OSIS-managed attendance, and habituation methods supported by exemplary behavior, persuasive advice, and structured supervision. Supporting and inhibiting factors arise from school leadership, teacher commitment, student readiness, availability of facilities, and school environment conditions. The study concludes that PAI teachers significantly contribute to strengthening students’ religious discipline and promoting a culture of congregational worship in schools.